The Mediating Effect of Listening Metacognitive Awareness between Test-Taking Motivation and Listening Test Score: An Expectancy-Value Theory Approach - Xu, Jian (Frontiers in Psychology, 2017)
The present study investigated test-taking motivation in a large-scale and high-stakes L2 listening testing context by applying Expectancy-Value Theory as the framework to conceptualize test-taking motivation. Specifically, this study was intended to examine the complex relationships among expectancy, importance, interest, listening anxiety, listening metacognitive awareness, and listening test score using data from a large-scale and high-stakes language test of Chinese first-year undergraduates. Structural equation modelling was used to examine the mediation effect of listening metacognitive awareness on the relationship between expectancy, importance, interest, listening anxiety, and listening test score. According to the results, test takers’ listening scores can be predicted by expectancy, interest, and listening anxiety significantly. To put it in a similar sense, the The relationship between expectancy, interest, listening test anxiety, and the listening test score was mediated relationship between each of the three elements and the listening test score was mediated by listening metacognitive awareness. The practical implications were discussed. The findings have implications on how to enhance test takers’ test taking moviation and listening metacognitive awareness, as well as on L2 teachers regarding how to do intervention in L2 listening classrooms.